O inventário como ferramenta de diagnóstico e conservação preventiva: estudo de caso da coleção "Santos de Casa" de Marcia de Moura Castro - Ana Martins Panisset (2011)
The main objective of this dissertation is to emphasize the process of developing an inventory of cultural goods and the management of this inventory, as indispensable tools for preventive conservation activities. Thus, the dissertation proposes the development and theimplementation of an inventory methodology for private collections of religious sculptures, aiming at creating [specific] protocols and ensuring more systematic approaches [to inventorization]. The Collection "Santos de Casa" (Household Saints), property of Marcia de Moura Castro was used as the object of study.